Psychological Service in Education - Anpilova M. A., Belous O. V. (Interactive science, 2021)
teaching and learning an academic discipline aimed at training and development of students, mastering a system of ideas about the content and structure of the psychological service in the education system, the legal basis for activities of the service, the main types and directions of pedagogic and psychological practical and typical issues within the competence of his work. The study of the discipline by students will contribute to the formation of their General and professional worldview, professionally important personal properties and qualities. The academic discipline contributes to the deepening and expansion of the basic professional training of students, as well as takes into account their educational needs.
Keywords: образование; деятельность; ребенок; система; развитие; психолог; education; служба; учреждение; activity; development; system; child; service; institution; psychologist